Observation of strong valley magnetic response in monolayer transition metal dichalcogenide alloys of Mo₀.₅W₀.₅Se₂ and Mo₀.₅W₀.₅Se₂/WS₂ heterostructures - Wu, Lishu (2022)
Monolayer transition metal dichalcogenide (TMD) alloys have emerged as a unique material system for promising applications in electronics, optoelectronics, and spintronics due to their tunable electronic structures, effective masses of carriers, and valley polarization with various alloy compositions. Although spin-orbit engineering has been extensively studied in monolayer TMD alloys, the valley Zeeman effect in these alloys still remains largely unexplored. Here we demonstrate the enhanced valley magnetic response in Mo0.5W0.5Se2 alloy monolayers and Mo0.5W0.5Se2/WS2 heterostructures probed by magneto-photoluminescence spectroscopy. The large g factors of negatively charged excitons (trions) of Mo0.5W0.5Se2 have been extracted for both pure Mo0.5W0.5Se2 monolayers and Mo0.5W0.5Se2/WS2 heterostructures, which are attributed to the significant impact of doping-induced strong many-body Coulomb interactions on trion emissions under an out-of-plane magnetic field. Moreover, compared with the monolayer Mo0.5W0.5Se2, the slightly reduced valley Zeeman splitting in Mo0.5W0.5Se2/WS2 is a consequence of the weakened exchange interaction arising from p-doping in Mo0.5W0.5Se2 via interlayer charge transfer between Mo0.5W0.5Se2 and WS2. Such interlayer charge transfer further evidences the formation of type-II band alignment, in agreement with the density functional theory calculations. Our findings give insights into the spin-valley and interlayer coupling effects in monolayer TMD alloys and their heterostructures, which are essential to develop valleytronic applications based on the emerging family of TMD alloys.